If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 4(-7) + 26 Multiply 4 * -7 y = -28 + 26 Combine like terms: -28 + 26 = -2 y = -2 Solving y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -2
| 6y=5y^2+1 | | [23-5t]=33 | | 1x^2+3x-4=0 | | 9x-64=8 | | -2x+2(4x+26)=10 | | (x-2)/41-2 | | v(v-5)=14 | | -2+2(4x+26)=10 | | v*2=7v | | x-2/41-2 | | 3x^2-10+7=0 | | 56+11=80+8x | | 2r^2-26r+72=0 | | x+8/x=-9 | | 8x+4y-12=0 | | 21x+31+9x+41=702 | | 6z=2/5 | | 21x+31+9x+41=701 | | 21x+31+9x+41=696 | | 21x+31+9x+41=691 | | 21x+31+9x+41=725 | | 21x+31+9x+41=727 | | 21x+31+9x+41=730 | | 6/(9+i) | | 1/2(12+4x-10) | | 4x+8+6=34 | | (x/x-8)+8=(8/x-8) | | 21x+31+9x+41=709 | | 4/9=x/1 | | a/2=a/9+1/2 | | 21x+31+9x+41=718 | | 6/y+8/y=2 |